UNREST AND UNFILLED STOMACHS: UNRAVELLING THE LINKAGE BETWEEN ARMED CONFLICT AND FOOD INSECURITY IN NORTH CENTRAL REGION OF NIGERIA - COMFORT FATIMOH SHEIDU; IRORO S. IZU (International Studies Journal)
This study investigates the link connecting armed conflict and food insecurity in Nigeria's North Central region. Due to resource competition, political and ethnic tensions, historical grievances, and religious extremism, the region has seen protracted armed conflicts. Food security has declined as an outcome of disruptions in agriculture, infrastructure, and market systems. Considering this, the purpose of this study is to shed light on the many linkages between food insecurity and armed conflicts in Nigeria's North Central region and also to suggest measures to address the challenges to enhancing food security conditions in the troubled region's armed conflict-affected settings. Therefore, unpacking the link between armed conflict-affected settings and various aspects of food insecurity is required. Data were gathered and examined in order to ascertain the current state of knowledge, study, and focus on various aspects of armed conflict and their disastrous effects on food insecurity in the region while using a scoping review technique to investigate the link between armed conflict and food insecurity concerns in Nigeria's north central region. The findings will help policymakers, practitioners, and researchers involved in conflict resolution and food security initiatives better understand the complex dynamics of armed conflict and food insecurity in the region. This research is critical for developing context-specific policies and interventions to tackle the challenges faced by conflict-affected communities while also promoting long-term peace and food security in Nigeria's North Central region.